Effect of Combination of Dark Chocolate and Herbal Ingredients for Dysmenorrhea in Late Adolescents - Rika Nurlaili Putri Azizah; Putri Anggreini; Fajar Prasetya (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2023)
About 55% of women experience dysmenorrhea. One of the foods that can reduce menstrual pain is dark chocolate. Other herbal ingredients such as turmeric, red ginger, moringa, sambiloto, and honey are also known to reduce pain. However, research on combination of dark chocolate with herbal ingredients has not been conducted. Therefore, this study aims to determine the effectiveness of dark chocolate with herbs in reducing menstrual pain. This test was conducted on 30 respondents who were divided into three groups, namely the positive control group (K), dark chocolate (C), and a combination of dark chocolate with herbs (C+H). Dark chocolate was combined with herbal ingredients consisting of turmeric, red ginger, moringa, sambiloto extract, and honey as a beverage 250 mL. The study is quantitative research with quasi-experimental method. Pain measurement using the Numeric Rating Scale (NRS) sheet was given before and 2 hours after treatment. The data was analyzed using paired t-test. State the results of the values obtained the combination of dark chocolate and herbs showed a significant reduction in pain before and after treatment (p<0.05). Based on these results, it was concluded that the combination of dark chocolate with herbs could be one of the therapies for dysmenorrhea.